Impact of perinatal asphyxia on parental mental health and bonding with the infant: a questionnaire survey of Swiss parents. Issue 1 (11th September 2017) - Horsch, Antje; Jacobs, Ingo; Gilbert, Leah; Favrod, Céline; Schneider, Juliane; Morisod Harari, Mathilde; Bickle Graz, Myriam
Abstract : Objective: To compare current mental health symptoms and infant bonding in parents whose infants survived perinatal asphyxia in the last 2 years with control parents and to investigate which sociodemographic, obstetric and neonatal variables correlated with parental mental health and infant bonding in the asphyxia group. Design: Cross-sectional questionnaire survey of parents whose children were registered in the Swiss national Asphyxia and Cooling register and of control parents (Post-traumatic Diagnostic Scale, Hospital Anxiety and Depression Scale, Mother-to-Infant Bonding Scale). Results: The response rate for the asphyxia group was 46.5%. Compared with controls, mothers and fathers in the asphyxia group had a higher frequency of post-traumatic stress disorder (PTSD) symptoms (p<0.001). More mothers (n=28, 56%) had a symptom diagnosis of either full or partial PTSD than controls (n=54, 39%) (p=0.032). Similarly, more fathers (n=31, 51%) had a symptom diagnosis of either partial or full PTSD than controls (n=19, 33%) (p=0.034). Mothers reported poorer bonding with the infant (p=0.043) than controls. Having a trauma in the past was linked to more psychological distress in mothers ( r =0.31 (95% CI 0.04 to 0.54)) and fathers ( r =0.35 (95% CI 0.05 to 0.59)). For mothers, previous pregnancy was linked to poorer bonding ( r =0.41 (95% CI 0.13 to 0.63)). In fathers, therapeutic hypothermia of the infant was related to less frequent PTSD symptoms ( r =−0.37 (95% CI −0.61 to −0.06)) and past psychological difficulties ( r =0.37 (95% CI 0.07 to 0.60)) to more psychological distress. A lower Apgar score was linked to poorer bonding ( r =−0.38 (95% CI −0.64 to −0.05)). Conclusions: Parents of infants hospitalised for perinatal asphyxia are more at risk of developing PTSD than control parents.